The nptA Gene of Vibrio cholerae Encodes a Functional Sodium-Dependent Phosphate Cotransporter Homologous to the Type II Cotransporters of Eukaryotes - Lebens, Michael (American Society for Microbiology, 2002)
The nptA gene of Vibrio cholerae has significant protein sequence homology with type II sodium-dependent phosphate (P(i)) cotransporters found in animals but not previously identified in prokaryotes. The phylogeny of known type II cotransporter sequences indicates that nptA may be either an ancestral gene or a gene acquired from a higher eukaryotic source. The gene was cloned into an expression vector under the control of an inducible promoter and expressed in Escherichia coli. The results demonstrate that nptA encodes a functional protein with activity similar to that of the animal enzyme, catalyzing high-affinity, sodium-dependent P(i) uptake with comparable affinities for both sodium and phosphate ions. Furthermore, the activity of NptA is influenced by pH, again in a manner similar to that of the NaPi-2a subtype of the animal enzyme, although it lacks the corresponding REK motif thought to be responsible for this phenomenon. P(i) uptake activity, a component of which appeared to be sodium dependent, was increased in V. cholerae by phosphate starvation. However, it appears from the use of a reporter gene expressed from the nptA promoter that none of this activity is attributable to the induction of expression from nptA. It is thus proposed that the physiological function of NptA protein may be the rapid uptake of P(i) in preparation for rapid growth in nutrient-rich environments and that it may therefore play a role in establishing infection.